Association of Health Literacy with Demographic Features, Health-Related Behaviors, and Health Risk Indicators among Egyptian Adults: Online Cross-Sectional Study - Hassan, Rana Gamal (AUC Knowledge Fountain, 2023)
Health literacy is recognized as a significant determinant of health. Limited health literacy is a growing issue worldwide. It has a significant role facing the rising trends of non-communicable diseases (NCDs) through improving its modifiable risk factors. Therefore, studying the association between health literacy and different health-related behaviors is very important to guide both healthcare professionals and policy makers to set up the proper interventions. Our study aims to a) examine the health literacy levels among Egyptian adults, b) investigate the association of health literacy relative to socio-demographic features, health related behaviors, and self-reported health status. This is a cross-sectional study where convenient sample of 358 Egyptian adults living in Greater Cairo were contacted online to participate in a self-administered survey. Statistical analysis was used to estimate the odds ratios (OR) between levels of health literacy and demographic features, health risk behaviors, and health status using binary logistic regression. The results showed that limited health literacy reaches 52%. Males, participants with below average monthly income, and those with chronic diseases are more likely to have limited health literacy, while participants with healthcare background and those who use at most 1 source searching for healthcare information are less likely to have limited health literacy. Limited health literacy has also been associated with physical inactivity, higher perceived mental stress rate, and sleeping hours less than 7 hours per day. Finally, the knowledge score of the participants on the main risk factors related to the most common non-communicable diseases was positively correlated with their health literacy score. Limited health literacy is a prevalent problem in Egypt, and further longitudinal national research is warranted to better identify the magnitude of the problem and establish casual associations between health literacy and demographic and behavioral factors.